Oh, the places you'll go! - Seuss, Dr. (New York : Random House, 1990)
Advice in rhyme for proceeding in life; weathering fear, loneliness, and confusion; and being in charge of your actions. "Don't be fooled by the title of this seriocomic ode to success; it's not 'Climb Every Mountain, ' kid version. All journeys face perils, whether from indecision, from loneliness, or worst of all, from too much waiting. Seuss' familiar pajama-clad hero is up to the challenge, and his odyssey is captured vividly in busy two-page spreads evoking both the good times (grinning purple elephants, floating golden castles) and the bad (deep blue wells of confusion). Seuss' message is simple but never sappy: life may be a 'Great Balancing Act, ' but through it all 'There's fun to be done.'
Keywords: Success -- Fiction; Stories in rhyme; Success -- Juvenile fiction; Children's poetry